Financial Liberalization and Monetary Policy Cooperation in East Asia - CHOW, Hwee Kwan (Institutional Knowledge at Singapore Management University, 2007)
As the countries in East Asia embark on financial liberalization, a key issue that confronts policymakers is the greater complexity of risks that is injected into the financial system. In particular, capital account liberalization may potentially increase the vulnerability of individual countries to external financial shocks. This paper advocates the optimally cascading of financial liberalization that is consistent across three dimensions: extent of domestic financial liberalization; the degree of exchange rate flexibility; and the scope of capital account liberalization. Unless the process of liberalization is properly managed, it could provoke destabilizing capital flows and lead to volatile exchange rates. Smooth responses to fluctuating capital flows require accelerated institutional reforms in individual countries and an upgraded regional financial infrastructure. We argue that informal monetary arrangements, sequenced from simple to more intensive commitments, can go a long way in improving sovereign and regional institutions both to handle ongoing financial liberalization and to promote intra-regional currency stability.